Should I stay or should I go? Predictors and effects of studying abroad during high school. (February 2021) - Hübner, Nicolas; Trautwein, Ulrich; Nagengast, Benjamin
Abstract: In an increasingly globalized and culturally diverse world, extended stays abroad during high school are considered important opportunities for acquiring and improving a variety of skills, most importantly, language achievement. This study examines both predictors and effects of studying abroad in an English-speaking country during high school, using population data from the second largest city in Germany ( N = 5361; 13% went abroad). In order to determine the most central predictors of studying abroad, we employed logistic regression models in which students' socioeconomic background emerged as the strongest predictor of studying abroad. To test the effects of studying abroad, we applied propensity score matching. Studying abroad had positive effects on standardized achievement, grades, and course choice in English, whereas it had hardly any effects on outcomes in math. Implications for studying abroad during high school and future research directions are discussed. Highlights: Students' SES is a key predictor of studying abroad during high school. Studying abroad during high school had positive effects on achievement in English. Barely any effects were found for outcomes in math.